Role of risk factors, clinical features and treatment modality in early detection and management of Buerger’s disease: a study from tertiary care centre Pondicherry - Kiruba, Krithika; Koranga, Himadra; Ramaraj, Chandrasekaran; Takalkar, Anant A. (International Surgery Journal, 2020)
Background: Thromboangiitis obliterans is a disease of unknown aetiology seen under 45 years of age with no form of treatment has been successful in offering the victims of this disease a cure nor even a long-term remission. Objective of the study was to study the role of different risk factors, clinical features and treatment modality in early detection and management of Buerger’s disease. Methods: This is an experimental study carried out in 50 cases of Buerger’s disease after obtaining a well-informed written consent in department of General Surgery in Aarupadai Veedu Medical College and Hospital. Period of study was from October 2015 to October 2017. Data was analysed with SPSS 23.0 version. Results: Majority were from 31-40 years age group i.e. 30 (60%). Left lower limb was involved in 52% subjects. 80% smoked more than 20 cigarettes per day. Signs of ischemia was present in all 50 patients. Gangrene of the limb was seen in 14 patients (28%). Out of 3 patients with recurrent pain, 2 (66.7%) were relieved. Ulcer healing occurred in 5 out of 6 patients i.e. 83.3% and intermittent claudication was relieved in 2 out of 7 patients i.e. 28.6%. Conclusions: Males are commonly involved in our study. Majority of patients were in age group 31-40 years. Smoking is an important and definite risk factor in relation with the development of Buerger’s disease. Lower limb is commonly involved. Majority of patients in our series were treated by conservative management.